Association Between Temporal Changes in Early Repolarization Pattern With Long‐Term Cardiovascular Outcome: A Population‐Based Cohort Study - Liu, Li‐Juan; Tang, Na; Bi, Wen‐Tao; Zhang, Ming; Deng, Xue‐Qiong; Cheng, Yun‐Jiu (Journal of the American Heart Association, 2022)
Background The prognostic value of early repolarization pattern (ERP) remains controversial. We aim to test the hypothesis that temporal changes in ERP are associated with increased risks for sudden cardiac death (SCD) and cardiovascular death. Methods and Results A total of 14 679 middle-aged participants from the prospective, population-based cohort were included in this analysis, with ERP status recorded at baseline and during 3 follow-up visits in the ARIC (Atherosclerosis Risk in Communities) study. We related baseline ERP, time-varying ERP, and temporal changes in ERP to cardiovascular outcomes. Cox models were used to estimate the hazard ratios (HRs) adjusted for possible confounding factors. With a median follow-up of 22.5 years, there were 5033 deaths, 1239 cardiovascular deaths, and 571 SCDs. Time-varying ERP was associated with increased risks of SCD (HR, 1.59 [95% CI, 1.25-2.02]), cardiovascular death (HR, 1.70 [95% CI, 1.44-2.00]), and death from any cause (HR, 1.16 [95% CI, 1.05-1.27]). Baseline ERP was also associated with 3 outcomes. Compared with those with consistently normal ECG findings, subjects with new-onset ERP or consistent ERP experienced increased risks of developing SCD and cardiovascular death. The time-varying ERP in women, White subjects, and anterior leads and J-wave amplitudes ≥0.2 mV appeared to indicate poorer cardiovascular outcomes. Conclusions Our findings suggest that baseline ERP, time-varying ERP, new-onset ERP, and consistent ERP were independent predictors of SCD and cardiovascular death in the middle-aged biracial population. Repeated measurements of the ERP might improve its use as a risk indicator for SCD.